2006
DOI: 10.1148/radiol.2411051271
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Electrode Radiofrequency Ablation Creates Confluent Areas of Necrosis: In Vivo Porcine Liver Results

Abstract: PURPOSE-To prospectively evaluate an impedance-based multiple-electrode RF ablation system for creation of confluent areas of hepatic coagulation in an in vivo porcine model. MATERIALS & METHODS-Pre-approval was obtained from our institutional research animal care and use committee. A prototype multiple-electrode RF system was created allowing switching between three electrically-independent electrodes at impedance spikes (30 Ω increase). Forty-two coagulation zones [single=18, cluster=12, multiple-electrode (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 32 publications
4
62
1
Order By: Relevance
“…It is known that internal cooling causes a "heat sink effect," which removes heat from the tissue next to the electrode, preventing tissue charring, increasing power deposition into the tissue, and thus producing larger coagulation zones than noncooled techniques [26]. With internal cooling, previous studies have obtained coagulation volumes of 6.7 cm 3 [27] and 5.76 cm 3 [28]. On the other hand, when internal cooling was combined with saline perfusion, the results showed even better efficiency in energy deposition [9,10], creating greater coagulation volumes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that internal cooling causes a "heat sink effect," which removes heat from the tissue next to the electrode, preventing tissue charring, increasing power deposition into the tissue, and thus producing larger coagulation zones than noncooled techniques [26]. With internal cooling, previous studies have obtained coagulation volumes of 6.7 cm 3 [27] and 5.76 cm 3 [28]. On the other hand, when internal cooling was combined with saline perfusion, the results showed even better efficiency in energy deposition [9,10], creating greater coagulation volumes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the minimum transverse diameter was significantly higher in group 2 than in group 1. This parameter is a limiting factor when determining the effectiveness of a particular ablation procedure [27] to ensure that the whole target volume is completely destroyed. Our results therefore suggest that the hybrid applicator could also create coagulations with a greater minimum transverse diameter.…”
Section: Burdío Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Recently, multiple-electrode RFA approaches, including the switching monopolar (SM) mode, bipolar mode and multipolar mode, have been attempted with each demonstrating efficiency in creating a larger ablation zone in liver tissue than in the standard monopolar RF technique. 2,[20][21][22][23][24][25][26] Theoretically, RFA in switching bipolar (SB) mode using multiple electrodes should further improve the thermal and electronic efficiency of RFA devices compared to conventional monopolar modes. However, until now, the efficacy of SB-RFA with internally cooled wet (ICW) electrodes, which allow simultaneous internal cooling and saline infusion, in creating 3-to 5-cm coagulation areas, have not been tested in previous in vivo studies.…”
mentioning
confidence: 99%
“…Thirdly, in vivo animal studies will have to be confirmed by a human clinical trial treating primary or secondary tumours in healthy and cirrhotic liver [15]. Unfortunately, a large-animal tumour model is not yet available [112]. Nevertheless ex vivo studies in explanted animal livers remain a good starting point for the pilot investigation and development of novel radiofrequency ablation techniques [113].…”
Section: Matrix Radiofrequency Ablationmentioning
confidence: 99%